Lacrosse Players, Not Terrorists: The Effects of the Western Hemisphere Travel Initiative on Native American International Travel and Sovereignty - Brian Kolva (Washington University Journal of Law & Policy, 2012)
Most sports fans would agree that a world baseball championship without Americans, a world hockey championship without Canadians, or a world golf championship without Scots—the respective creators of the games—would be inadequate and disappointing. But this was precisely the situation lacrosse fans encountered in July 2010, when the Federation of International Lacrosse World Championship tournament opened in Manchester, England. The team representing the sport’s creators was holed up in an airport hotel three thousand miles away, embroiled in a bureaucratic dispute over passports. That absent team was the Iroquois Nationals, a team comprised of Native American players from the six federally recognized tribes that form the Iroquois Confederacy. The dispute was the culmination of multiple poor policy decisions made by the U.S., United Kingdom, and Iroquois governments. Not only did missing the beginning of the tournament impose significant financial costs on the team and adversely impact their chances of winning the tournament, it also highlighted a much greater problem: the future of the Iroquois identity. The issues of tribal identity and sovereignty are issues that Native Americans and the U.S. government have grappled with ever since the Revolutionary War concluded. These issues have resulted in a number of embarrassing incidents for the United States and Native Americans, a tremendous amount of bloodshed, and an incalculable amount of hard feelings on both sides. The Iroquois Nationals’ passport dispute encapsulates several persistent problems with federal Indian policy and also exemplifies how post-9/11 national security policy, specifically the WHTI, affects tribal sovereignty. Part II of this Note discusses Indian and federal constructions of the concept of tribal sovereignty; a history of federal Indian policy; the history of lacrosse in the Iroquois culture; and the post-9/11 national security policies with regards to travel documents, specifically new passport requirements. Part III of this Note analyzes the problems the new laws created for Indians, specifically the inability to attain full recognition as sovereign people by placing restrictions on the use of tribal documents. The mistakes made by the three principal actors (United States, United Kingdom, and the Iroquois) in creating this passport dispute are examined, concluding that with minimal cooperation and a proper, uniform enforcement of the applicable laws, the situation could have been avoided entirely. The analysis of the infringement that new passport requirements have on tribal sovereignty necessitates an examination of potential future sources of conflict, which are also identified in Part III. Part IV contains numerous proposals to avoid similar problems in the future and a discussion of how the Manchester situation could have been amicably resolved. The proposals specify measures that should have been (or should be) taken by each of the three principals in order to maintain the balance between protecting national security interests and tribal sovereignty.
Keywords: lacrosse world championship; native american lacrosse players; Iroquois Nationals; Western Hemisphere Travel Initiative